Variation of Serum Sodium and Potassium in Acute Watery Diarrhea - Muhammad Usman Rafique, Imran Yasin, Husnul Hayat, Rizwan Mahmood, Khurram Nawaz, Sanwal Sardar Nawaz (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diarrhea is one of the leading causes of mortality and morbidity in children less than 5 years of age in developing countries. Electrolyte abnormalities are common in children with diarrhea that may remain unrecognized and result in mortality and morbidity. Objective: To determine the frequency of serum sodium and potassium disturbances in acute watery diarrhea. Methodology: This cross sectional study was conducted at Paediatric Ward, Lahore General Hospital, Lahore from 1st July 2016 to 31st December 2016 and 280 patients of acute diarrhea were enrolled. Venous blood samples for serum sodium and potassium were done at the time of admission and sent to the hospital lab and followed. All the cases were rehydrated according to WHO guidelines. Results: 61.8% patients had electrolyte abnormalities. Most significant electrolyte abnormality was hypokalemia 33.6%, followed by hyponatremia 22.5% and hypernatremia 5.7%. Conclusion: The electrolyte abnormalities were more common in infants and the electrolyte abnormalities increased as the duration of diarrhea prolonged. Keywords: Acute diarrhea, Hyponatremia, Hypokalemia, Hypernatremia